IMPLEMENTASI KONSELING INDUVIDU DAN KONSELING KELOMPOK UNTUK PEMBINAAN AKHLAK DI MADRASAH ALIYAH ISLAMIC CENTRE SUMATERA UTARA - Andi Nova (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2017)
The objective of this research to describe implementation of individual counseling and clouster counselingin Islamic centre senior high school in the north of sumatera, with the details in order to describe how toimplement individual counseling and cluster counseling and any obstacle who happen in implementationindividual counseling and cluster counseling. The method of this research is qualitative descriptive, whothe thing became instrument researcher asset, the database has acquired is from two resources, that isprimary and secondary, with the technique is aggregation database by observation, interview, and documentation,and analysis database technique be done reductionly, database presentation, and conclusion.The technique of database validity can be done with credibility, trasnsferability, dependability, confirmability.